Novel monofunctional and bifunctional boronic acid‐functionalized squarylium dyes as precolumn and on‐column labels for protein analysis by capillary electrophoresis with laser‐induced fluorescence. Issue 2 (25th October 2018) - Sebaiy, Mahmoud M.; El‐Shanawany, Abdullah A.; Baraka, Mohamed M.; Abdel‐Aziz, Lobna M.
Abstract : This article presents a continuous capillary electrophoresis with laser‐induced fluorescence (CE‐LIF) following spectral studies of the noncovalent interactions between novel Squarylium Boronic Acid 4 (SQ‐BA4) & Squarylium Diboronic Acid 2 (SQ‐DBA2) squarylium dyes and human serum albumin (HSA). Two protocols were used wherein the on‐column‐labeling protocol was found to be more sensitive than the precolumn one by showing a better enhancement in the peak area of the HSA–dye complex besides lower limits of detection (LODs) for HSA. Also, stability studies were conducted with or without HSA using precolumn‐labeling mode over one week exhibiting the superiority of SQ‐BA4 to SQ‐DBA2. Then, a mixture containing three model proteins, HSA, β‐lactoglobulin B, and transferrin, was labeled on‐column with both dyes and completely resolved by CE‐LIF after optimization of several parameters. Both dyes provided lower LODs for HSA than those of β‐lactoglobulin B and transferrin with higher sensitivities. In addition, the SQ‐BA4 dye showed again greater sensitivities with all the three proteins than SQ‐DBA2. Abstract : Novel SQ‐BA4 & SQ‐DBA2 squarylium dyes can be used as fluorescent probes for human serum albumin, β‐lactoglobulin B, and transferrin through noncovalent interaction using capillary electrophoresis with laser‐induced fluorescence.